Nyctaginaceae: A taxonomic treatment for the Flora of Namibia - Struwig, Madeleen; Klaassen, Esmerialda S; Kwembeya, Ezekiel G (Phytotaxa, 2015)
A taxonomic treatment of the Nyctaginaceae for the Flora of Namibia is presented, including the description of the family, keys to the genera and species, nomenclature, descriptions of all generic and infrageneric taxa, as well as data about the habitat, elevation, flowering time and distribution. Namibia is the centre of diversity for the family in southern Africa and is represented by four genera and 17 species distributed throughout the country. The names Mirabilis divaricata, Boerhavia atomaria, B. viscosa, B. coccinea f. parcehirsuta and B. stellata are typified on specimens respectively preserved at BM, PH, G, B and an illustration.